Changes in the Morphological Characteristics and Body Composition of Elite Montenegrin Football Players during the Competition Period - Dusko Bjelica; Jovan Gardasevic; Ivan Vasiljevic; Bojan Masanovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The goal of this research was to assess the quantitative and qualitative changes imposed by training and competition with help of selected variables of morphological characteristics and body composition which were measured in elite football players of First Montenegrin Telecom League at two different time points during the competition period. In this study 28 male football players (22.5±5.87 yrs.) of OFK Titograd from Podgorica who compete in the First Montenegrin Telecom League were enrolled. The measurements were carried out in January and then again, after 30 days, in February. Morphological characteristics in the body composition were evaluated by a battery of 11 variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, back skinfold, abdominal skinfold, body mass index, fat percentage and muscle mass. The differences in morphological characteristics and the composition of the body in two periods during the competition period were determined by using a discriminatory parametric procedure with t-test for small independent samples. It was found that in football players of OFK Titograd in 30 days significant changes are observed for 3 variables, for upper arm skinfolf - triceps, back skinfold and abdomen skinfold.